THE TEACHERS' CLINIC. - Carson, A. B.; Peirce, Richard F.; Corbin, Donald A.; La Salle, Brother; Stevenson, R. E.; MacDougall, Colville (The Accounting Review, 1956)
Abstract The article focuses on electronic data processing in the accounting curriculum. The author mentions that growing development in the field of electronic computers and their potential use in processing business and accounting data has prompted course offering in this area. He enumerates the content that should be included in a university-level course in the area of accounting. He brings into consideration the programming of a system which includes planning, systems analysis, flow charting, coding and the other functions necessary to integrate the new system into business. He discusses the question of whether an electronic computer is necessary to teach a course or not, stating that it is necessary for elementary courses in data processing. Questions pertaining to the requisites for courses, the department which should offer system courses and the text material to be used in such courses and the availability of instructors in data processing and the training necessary for prospective instructors have been examined.